Associations of pre‐existing co‐morbidities with skeletal muscle mass and radiodensity in patients with non‐metastatic colorectal cancer. Issue 4 (19th April 2018) - Xiao, Jingjie; Caan, Bette J.; Weltzien, Erin; Cespedes Feliciano, Elizabeth M.; Kroenke, Candyce H.; Meyerhardt, Jeffrey A.; Baracos, Vickie E.; Kwan, Marilyn L.; Castillo, Adrienne L.; Prado, Carla M.
Abstract: Background and aim: Co‐morbidities and computerized tomography‐measured muscle abnormalities are both common in cancer patients and independently adversely influence clinical outcomes. Muscle abnormalities are also evident in other diseases, such as diabetes and obesity. This study examined for the first time the association between co‐morbidities and muscle abnormalities in patients diagnosed with colorectal cancer (CRC). Methods: This cross‐sectional study included 3051 non‐metastatic patients with Stages I–III CRC. Muscle abnormalities, measured at diagnosis, were defined as low skeletal muscle mass index (SMI) or low skeletal muscle radiodensity (SMD) quantified using computerized tomography images using optimal stratification. Co‐morbidities included in the Charlson index were ascertained. χ 2 tests were used to compare the prevalence of co‐morbidities by the presence or absence of each muscle abnormality. Logistic regressions were performed to evaluate which co‐morbidities predicted muscle abnormalities adjusting for age, sex, body mass index, weight change, cancer stage, cancer site, race/ethnicity, and smoking. Results: Mean age was 63 years; 50% of patients were male. The prevalence of low SMI and low SMD were 43.1% and 30.2%, respectively. Co‐morbidities examined were more prevalent in patients with low SMD than in those with normal SMD, and most remained independent predictors of low SMD after adjustment for covariates. Co‐morbidities associated with higher odds of low SMD included myocardial infarction [odds ratio (OR) = 1.77, P = 0.023], congestive heart failure (OR = 3.27, P < 0.001), peripheral vascular disease (OR = 2.15, P = 0.002), diabetes with or without complications (OR = 1.61, P = 0.008; OR = 1.46, P = 0.003, respectively), and renal disease (OR = 2.21, P < 0.001). By contrast, only diabetes with complications was associated with lower odds of low SMI (OR = 0.64, P = 0.007). Conclusions: Prevalence of muscle abnormalities was high in patients with non‐metastatic CRC. Pre‐existing co‐morbidities were associated with low SMD, suggestive of a potential shared mechanism between fat infiltration into muscle and each of these co‐morbidities.